Analisis Perkembangan Karakter Siswa Ditinjau Dari Gaya Belajar Pada Mata Pelajaran Ipas Siswa Kelas II Sdk Santa Carmen Salles Kota Kupang - Beribe, Lusia; Nitte, Yulsi Marselina; Naiti, Cornelia A. (JUPE : Jurnal Pendidikan Mandala, 2025)
Analysis of Student Character Development Reviewed from Learning Styles in the Science Subject of Grade II Students of SDK Santa Carmen Salles, Kupang City. Thesis of Elementary School Teacher Education Study Program, Faculty of Teacher Training and Education, Citra Bangsa University. Advisor 1 Yulsy M. Nitte, SH,.M.Pd and Advisor II Cornelia A. Naitili, S.Pd,.M.Pd.This research aims to analyze the development of student character in terms of learning styles in the Natural and Social Sciences (IPAS) subjects of class II SDK Santa Carmen Salles, Kupang City. The characters studied include responsibility; discipline and care for the environment, while the learning styles studied consist of visual, auditory and kinesthetic styles. The research method used is descriptive qualitative with data collection techniques through observation, interviews and documentation. The results of the study showed that students' learning styles influenced their character development. Students with a visual learning style have good character development in terms of responsibility and discipline. Auditory students show balanced character development, including responsibility, discipline, and environmental awareness through verbal interactions in group discussions. Kinesthetic students have a more prominent environmental awareness character through active involvement in practical activities, such as planting trees and maintaining the cleanliness of the school environment.The subject of science and natural sciences plays an important role in supporting the formation of student character through learning activities that are relevant to each student's learning style. This study concludes that a varied learning approach based on learning styles can effectively encourage the development of student character.